New Black Gods: Arthur Huff Fauset and the Study of African American Religions - Curtis, Edward E. IV (Religion in North America, 2009)
Taking the influential work of Arthur Huff Fauset as a starting point to break down the false dichotomy that exists between mainstream and marginal, a new generation of scholars offers fresh ideas for understanding the religious expressions of African Americans in the United States. Fauset's 1944 classic, Black Gods of the Metropolis, launched original methods and theories for thinking about African American religions as modern, cosmopolitan, and democratic. The essays in this collection show the diversity of African American religion in the wake of the Great Migration and consider the full field of African American religion from Pentecostalism to Black Judaism, Black Islam, and Father Divine's Peace Mission Movement. As a whole, they create a dynamic, humanistic, and thoroughly interdisciplinary understanding of African American religious history and life. This book is essential reading for anyone who studies the African American experience.